The early Iron Age metal hoard from the Al Khawd area (Sultan Qaboos University), Sultanate of Oman - Al-Jahwari, Nasser Said Ali, (Archaeological heritage of Oman ;, 2021)
Numerous metallic artefacts, deposited in a hoard in ancient times, came to light by chance on the campus of the Sultan Qaboos University in Al Khawd, Sultanate of Oman. Mostly fashioned from copper, these objects compare well with numerous documented artefact classes from south-eastern Arabia assigned to the Early Iron Age (1200-300 BCE).